2018
DOI: 10.1186/s12873-018-0176-3
|View full text |Cite
|
Sign up to set email alerts
|

The mission characteristics of a newly implemented rural helicopter emergency medical service

Abstract: BackgroundPhysician-staffed helicopter emergency services (HEMS) can provide benefit through the delivery of specialist competence and equipment to the prehospital scene and through expedient transport of critically ill patients to specialist care. This paper describes the integration of such a system in a rural Swedish county.MethodsThis is a retrospective database study recording the outcomes of every emergency call centre dispatch request as well as the clinical and operational data from all completed missi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
3
20
1
Order By: Relevance
“…In the future electronic transfer of measurements could be used to reduce typing errors, however, this does not eliminate the errors in measurement per se. The rate of cancelled or denied missions in the Finnish HEMS system is substantially higher than reported elsewhere [6,7,21,22]. Technical reliability of the service seems to be excellent and it contributed to the cancellation rate minimally.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In the future electronic transfer of measurements could be used to reduce typing errors, however, this does not eliminate the errors in measurement per se. The rate of cancelled or denied missions in the Finnish HEMS system is substantially higher than reported elsewhere [6,7,21,22]. Technical reliability of the service seems to be excellent and it contributed to the cancellation rate minimally.…”
Section: Discussionmentioning
confidence: 62%
“…Key findings of this study were that in the Finnish HEMS system a large proportion of missions are cancelled or denied, and a relatively small percentage of patients are transported by helicopter. We also found that the medical problem for HEMS dispatch differ from comparable systems [7,8,21].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The search strategy led to the inclusion of 38 articles describing 20 HEMS models from 12 different countries. Five model descriptions included specific mention of a joint HEMS and inter-facility care function: Australia (New South Wales) [2]; Australia (Victoria) [3]; Eastern Denmark [4]; Norway [5]; Sweden (Dalarna) [6]. The remaining 15 models described a HEMS function only.…”
Section: Resultsmentioning
confidence: 99%
“…The study conducted by Kottmann et al in Switzerland concerning HEMS missions to patients with body injuries showed that the clinical status of the patients was mild and moderate (NACA 1-3) [23]. Studies by Kornhall et al concerning HEMS missions in rural areas in Sweden and HEMS missions in Norway conducted by Østerås et al, revealed that the average NACA score was 4 [22,29]. In the study conducted by Newgard et al lower GCS, lower systolic blood pressure, abnormal number of breaths and pulse, were observed more often in patients treated in urban areas [26].…”
Section: 46%) the Analysis Carried Out Bymentioning
confidence: 99%